2006
DOI: 10.1117/12.645711
|View full text |Cite
|
Sign up to set email alerts
|

High quality laser milling of ceramics, dielectrics and metals using nanosecond and picosecond lasers

Abstract: Laser milling of industrial materials like ceramics, dielectrics and metals is of significant commercial interest for microfabrication of micro-moulds and other micro-system devices. 2.5D laser machined structures were generated in alumina, tungsten and steel substrates using a nanosecond copper vapour laser (511nm) at 10 kHz. Preliminary results in fused silica, alumina and steel are also presented from a high repetition rate amplified mode-locked picosecond Nd:vanadate laser. It is shown that high quality su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…They reported that both nanosecond and picosecond lasers can be used for high quality laser micromilling of ceramics that is difficult to machine with ultrahigh precision using conventional methods. Both laser types were capable of excellent surface finish with relatively high material removal rates [30,31]. Liu et al, 2007, confirmed precise, melt-free ultrafast laser microstructuring of ceramic alumina.…”
Section: Laser Micromachining Of Ceramicsmentioning
confidence: 60%
“…They reported that both nanosecond and picosecond lasers can be used for high quality laser micromilling of ceramics that is difficult to machine with ultrahigh precision using conventional methods. Both laser types were capable of excellent surface finish with relatively high material removal rates [30,31]. Liu et al, 2007, confirmed precise, melt-free ultrafast laser microstructuring of ceramic alumina.…”
Section: Laser Micromachining Of Ceramicsmentioning
confidence: 60%
“…Figure 9 shows the resulting ablation depth and the corresponding roughness for the interlayer rotation for 0 , 11 and 90 , while the rotation by 11 per layer had no influence on the ablation depth, the rotation by 90 led to a depth increase by approximately 13%. The influence of both, the orientation [ 34 ] and the order [ 35 ] of the laser scan path has been previously studied for several processes and materials, with a recommendation to rotate the angle between consecutive layers to improve process performance [ 36 , 37 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Scanning speed, laser power, and pulse frequency are the main considerations that influence laser processing and can once in a while be adjusted without changing the laser sort with a couple of special cases. While machining, nano and picoseconds lasers micro milling is a suitable method to the conventional process for producing ultra high precision products from difficult to cut materials [3]. The value of the depth of evacuated material decides the exactness of parts created through a layer manufacturing technology.…”
Section: Figure 1 Schematic Diagram Of Laser Micro-machiningmentioning
confidence: 99%
“…(3) 4Where i = number of attributes (1, 2, 3) k = number of experimental runs (1,2,3,9) (k) = original sequence = sequence after the data pre-processing (k) = maximum value of (k) Min (k) = minimum value of (k) = desired value. Fuzzy Tool which was available in matlab lab (2014a) software was used to get MPCI.…”
Section: Table 4 S/n Ratios Of D and Ramentioning
confidence: 99%